Aesthetic education and social network: cultivating receptive attention in adolescentes - Labrie, Marie-Pierre (2025)
On social media, adolescents are exposed to a vast quantity of images and sounds, continuously. The hyperconnectivity in which they evolve has a significant impact on the forms of their attention to available content and, by extension, to artworks shared on connected platforms. In this context, aesthetic appreciation, which requires time and sensitive attention, can represent a challenge. This article examines this issue by outlining a theoretical framework around the notions of attention, connected copresence, education for viewing and attention, and artistic and pedagogical détournement. Then, it proposes the analysis of a narrative of appreciation activities that took place in art classrooms at secondary school in Quebec. From this narrative, the article identifies pedagogical orientations promoting differentiated attention, intersubjectivity, and the processual nature of copresence to educate about seeing.